The Influence of Teacher Personality on Student Motivation and Learning Outcomes: A Systematic Review from an Economics of Education Perspective - Ananada, Ananada (PERFECT EDUCATION FAIRY, 2025)
Teacher personality plays a strategic role in shaping student motivation and learning outcomes, particularly within the context of the economics of education, which emphasizes the efficiency and effectiveness of the learning process. This study aims to examine the influence of teacher personality dimensions—encompassing teaching behavior, organizational behavior, and socio-emotional behavior—on student motivation and learning achievements. Utilizing a Systematic Literature Review (SLR) approach, this article analyzes 30 relevant scholarly articles to identify patterns of relationships between these variables. The findings indicate that teacher personality plays a significant role in creating a productive learning environment, enhancing student participation, and directly impacting academic performance. This research underscores the importance of personality development and soft skills training for educators to achieve optimal learning outcomes within the framework of education-based economic development.